Budget Analysis with Accurate 5: A Case Study of UD XYZ Wood Furniture, Indonesia - Raharjo, Sabrina Nahidah; Setiawan, Mohamad Arief; Athoillah, Ahmad Saifi (JBS Nexus, 2025)
A budget is an essential tool used by companies for cost planning. Accurate 5 Enterprise is a budgeting software that facilitates budget analysis. This research focuses on UD XYZ Trading Business, a company producing furniture from teak wood in Jombang, East Java, Indonesia. The objective is to prepare a production cost budget for UD XYZ and apply the budgeting feature in Accurate 5 Enterprise to analyze its realization. This study employs a quantitative research approach with an applied focus. Data sources include both primary and secondary data obtained through document studies and interviews. The analysis technique utilizes the Least Square method to forecast sales and production cost budgets for 2024. The findings indicate that the budget comparison on the income statement shows a 14% variance, implying that UD XYZ was unable to achieve the projected sales budget. The primary influencing factors are sales levels that did not meet the budget target and discrepancies in standard cost control for raw material procurement between January and March 2024.